Identifying turbulence features hindering swimming capabilities of grass carp larvae (Ctenopharyngodon idella) through submerged vegetation. Issue 1 (15th March 2022) - Tinoco, R. O.; Prada, A. F.; George, A. E.; Stahlschmidt, B. H.; Jackson, P. R.; Chapman, D. C.
Abstract: Aquatic vegetation can provide habitat and refuge for a variety of species in streams. However, the flow features generated by submerged patches of vegetation can also pose a challenge for fish larvae. We conducted a series of experiments with live grass carp larvae (starting ∼50 h post hatch) in a laboratory racetrack flume, using a submerged array of rigid cylinders to mimic vegetation. We used particle image velocimetry to characterize the flow field, and particle tracking velocimetry to obtain position and displacement of the fish. Four speeds and two submergence ratios were investigated. In contrast with previous studies with grass carp eggs, our data showed an active response from larvae to determine their position. Our study shows that: (1) mean velocity by itself is not a reliable predictor, as some larvae will seemingly prefer to be in areas of higher speeds with lower shear and turbulence, (2) turbulence characteristics can be used to identify areas avoided by larvae, (3) turbulence length scales are relevant to determine spatial distribution of larvae and their swimming capabilities within and above vegetated patches and similar roughness elements in streams. These findings can inform the design of monitoring and control strategies in rivers based on turbulence and turbulence scales generated by natural and man-made instream structures.